2004
DOI: 10.1007/bf03167030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on carbon tetrachloride-induced changes in rat serum

Abstract: Carbon tetrachloride (CCl4) is a volatile organic chemical, which causes tissue damage, especially to the liver and kidney. In experimental animals it has been shown to be carcinogenic. This study was designed to evaluate the effects of exogenous melatonin administration on the CCl4-induced changes of some biochemical parameters in rat blood. Twenty-four male Wistar rats were randomly divided into three equal groups: Control, CCl4 and CCl4 plus melatonin (CCl4+MEL). Rats in CCl4 group were injected subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…Posttreatment of LPME with CCl 4 resulted in the recovery of antioxidant enzymes activities and depleted TBARS contents, thus proving a best antioxidant plant . Similar observations were also observed by cotreatment of caffeic acid phenyl ester (Ogeturk et al, 2004) and Digera muricata (Khan et al, 2009) against CCl 4 treatment. It has been reported that most reactive CCl 3 Á radical combines are fatty acids, nucleic acids and are converted into trichloromethyl peroxy radical (CCl 3 OO Á ) in the presence of oxygen, inducing lipid peroxidation that in turn react with DNA to form a mutagenic pirimedopurinone adduct (M1G) of deoxyguanosine and DNA damages/fragmentation.…”
Section: Discussionsupporting
confidence: 87%
“…Posttreatment of LPME with CCl 4 resulted in the recovery of antioxidant enzymes activities and depleted TBARS contents, thus proving a best antioxidant plant . Similar observations were also observed by cotreatment of caffeic acid phenyl ester (Ogeturk et al, 2004) and Digera muricata (Khan et al, 2009) against CCl 4 treatment. It has been reported that most reactive CCl 3 Á radical combines are fatty acids, nucleic acids and are converted into trichloromethyl peroxy radical (CCl 3 OO Á ) in the presence of oxygen, inducing lipid peroxidation that in turn react with DNA to form a mutagenic pirimedopurinone adduct (M1G) of deoxyguanosine and DNA damages/fragmentation.…”
Section: Discussionsupporting
confidence: 87%
“…The decrease in serum protein content might be ascribed to liver damage caused by CCl 4 as reports indicate that liver damage causes decreased amino acid uptake or hepatic protein synthesis (El-Shenawy & Abdel-Nabi, 2006). As reported in other studies (Ogeturk et al, 2004) CCl 4 administration decreased serum urea levels considerably in comparison with control rats which marginally increased towards normalization in groups pretreated with F. racemosa extracts. However, some investigators have reported an increase in serum urea concentrations in CCl 4 -treated rats and attributed these changes in urea levels to the reduction in the glomerular filtration rate as a result of CCl 4 intoxication, since the serum concentration of these two parameters depends largely on the glomerular filtration (Moawad, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…The hepatotoxic effects of CCl 4 are largely due to its active metabolite, trichloromethyl radical (Johnston & Kroening, 1998;Srivastava et al, 1990). It is well established that CCl 4 administration causes a significant decrease in serum urea, total protein and albumin levels (Ogeturk et al, 2004) and in the present investigation a significant decrease in the levels of total protein, albumin and albumin/globulin ratio was observed. However, pretreatment with the extracts of F. racemosa significantly restored the serum protein levels nearer to control levels.…”
Section: Discussionsupporting
confidence: 75%
“…The LDH and γ-GT activities were significantly elevated in serum of CCl 4 treated group of mice. The CCl 4 caused significant increases in LDH (Raja et al, 2007) as well as γ-GT (Ogeturk et al, 2004) activities have been reported.…”
Section: Discussionmentioning
confidence: 89%